Mode of birth and medical interventions among women at low risk of complications: A cross-national comparison of birth settings in England and the Netherlands. - Ank de Jonge; Lilian Peters; Caroline C Geerts; Jos J M van Roosmalen; Jos W R Twisk; Peter Brocklehurst; Jennifer Hollowell (PLoS ONE)
Objectives To compare mode of birth and medical interventions between broadly equivalent birth settings in England and the Netherlands. Methods Data were combined from the Birthplace study in England (from April 2008 to April 2010) and the National Perinatal Register in the Netherlands (2009). Low risk women in England planning birth at home (16,470) or in freestanding midwifery units (11,133) were compared with Dutch women with planned home births (40,468). Low risk English women with births planned in alongside midwifery units (16,418) or obstetric units (19,096) were compared with Dutch women with planned midwife-led hospital births (37,887). Results CS rates varied across planned births settings from 6.5% to 15.5% among nulliparous and 0.6% to 5.1% among multiparous women. CS rates were higher among low risk nulliparous and multiparous English women planning obstetric unit births compared to Dutch women planning midwife-led hospital births (adjusted (adj) OR 1.89 (95% CI 1.64 to 2.18) and 3.66 (2.90 to 4.63) respectively). Instrumental vaginal birth rates varied from 10.7% to 22.5% for nulliparous and from 0.9% to 5.7% for multiparous women. Rates were lower in the English comparison groups apart from planned births in obstetric units. Transfer, augmentation and episiotomy rates were much lower in England compared to the Netherlands for all midwife-led groups. In most comparisons, epidural rates were higher among English groups. Conclusions When considering maternal outcomes, findings confirm advantages of giving birth in midwife-led settings for low risk women. Further research is needed into strategies to decrease rates of medical intervention in obstetric units in England and to reduce rates of avoidable transfer, episiotomy and augmentation of labour in the Netherlands.